2018
DOI: 10.3892/ol.2018.8058
|View full text |Cite
|
Sign up to set email alerts
|

Sterol regulatory element-binding protein 1 cooperates with c-Myc to promote epithelial-mesenchymal transition in colorectal cancer

Abstract: Abstract. Metastasis is the primary cause of mortality in colorectal cancer (CRC), the mechanism of which remains unclear. In the present study, by detecting mRNA expression using a reverse transcription-quantitative polymerase chain reaction (qPCR), it was revealed that sterol regulatory element-binding protein 1 (SREBP1) is highly expressed in CRC. Using a cell wound healing assay and a cell invasion assay, a novel metastasis-promoting role for SREBP1 in CRC was identified. Furthermore, snail family transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Interestingly, other studies have reported that E‐cadherin suppression by the SNAIL/HDAC1/2 complex regulates metastasis in pancreatic cancer (PC) [73] and CRC [74], consistent with the hypothesis proposed in the BC study. Another study revealed that miR‐18a inhibits the proliferation of adult pancreatic progenitor cells by suppressing the activity of the proliferation‐related PI3K/AKT and ERK signaling pathways [75].…”
Section: Main Textsupporting
confidence: 86%
“…Interestingly, other studies have reported that E‐cadherin suppression by the SNAIL/HDAC1/2 complex regulates metastasis in pancreatic cancer (PC) [73] and CRC [74], consistent with the hypothesis proposed in the BC study. Another study revealed that miR‐18a inhibits the proliferation of adult pancreatic progenitor cells by suppressing the activity of the proliferation‐related PI3K/AKT and ERK signaling pathways [75].…”
Section: Main Textsupporting
confidence: 86%
“…Furthermore, the same group showed that MYC directly binds the promoter of SNAIL [ 172 ]. Recently, it has been reported that the SREBP1 transcription factor facilitates the binding of MYC to the SNAIL promoter in colorectal cancer cells, thereby accelerating SNAIL expression, EMT, and migration [ 173 ]. SNAIL is named the master regulator of EMT because it exerts different functions in the process.…”
Section: Myc–the Regulator Of Emt and Metastasismentioning
confidence: 99%
“…The epithelial–mesenchymal transition (EMT) is a biological process through which epithelial cells lose their polarity and become mesenchymal cells, gaining migratory properties that increase invasiveness in cancer progression. 9 , 10 Growing evidence suggests that the EMT is associated with metastasis and occurs during the development of various carcinomas, including CC. 11 Numerous signaling pathways are involved in the EMT process, including the Wnt, Notch, nuclear factor-kappa B, TGF-β, and RTK/Ras.…”
Section: Introductionmentioning
confidence: 99%